JOINT DEGREES IN GEOGRAPHY HIGHER EDUCATION: POTENTIALITIES AND CONSTRAINTS - Teresa Barata-Salgueiro; Herculano A. P. Cachinho (European Journal of Geography)
In this text we stress the importance of joint degrees in Geography and go over some forms of organisation and problems that these programmes present in higher education institutions. Joint degrees are a very interesting example of higher education co-operation, with numerous advantages for both participants and society as a whole. They play a fundamental role in constructing a Europe of cultures and knowledge based on an understanding and respect for difference. Joint degrees can facilitate the implementation of the Bologna Process and help carry out the Lisbon Agenda by promoting knowledge, improving student mobility, and enhancing the competitiveness of universities. We discuss the advantages of joint degrees in general, and those of geography in particular, analyse the most common programme models and consider problems raised by the implementation of joint programmes and, finally, conclude with some suggestions.